External Reference Standards or Relative Response Factors: Considerations for Quantitation of Impurities in Pharmaceuticals - article Editorial (Разработка и регистрация лекарственных средств, 2021)
Accurate and reproducible quantitation of impurities in pharmaceuticals is an important part of drug development. Impurities must be controlled to levels that will ensure the quality of the product is as good or better than the quality of materials used in preclinical safety studies and clinical trials. International Council for Harmonisation (ICH) Q3A and Q3B guidelines for drug substances and drug products, respectively, provide regulatory expectations for investigation and control of impurities including process-related substances and degradation products. Thresholds for identification and safety qualification of impurities can be based on relative percentages or directly in milligrams of exposure, depending on the nature of drug substances and products1. Therefore, an accurate assessment of impurity levels is needed both to guide development efforts and during the entire lifecycle of the drug.